Experimental Investigations of the Plasma Arc Cutting of AISI 1020 Carbon Steel Plate - Algodi, Samer Jasim Mahmood; Salman, Abdulhakeem Amer (Al-Nahrain Journal for Engineering Sciences, 2024)
The current study presents the plasma cutting process of 2 mm thickness of AISI 1020 carbon steel. The experiment conducted by taking into the account the effect of two process parameters, including cutting current of 15 and 20 A with cutting speed in range of 500 - 4000 mm/min, on the kerf formation, microstructure and microhardness.The results showed that at low cutting current of 15 A the melting occurred at the workpiece surface without cutting action. Increase the current to 20 A led to full penetration of the workpiece material at low and high cutting speed, with kerf width between 1.26 mm and 1.1 mm for cutting speed of 500 mm/ min and 4000 mm/ min, respectively. The plasma arc cutting speed has a high impact on the heat-affected zone HAZ and microstructure development with coarse grains at the HAZ at low cutting speed of 500 mm/min and constant current of 20A, increase the plasma cutting speed led to decreasing the grain size. The microstructure of the HAZ exhibited a presence of perlite and ferrite with some martensite structure. The highest microhardness of the HAZ of 220.8 HV was found in the sample processed at 20 A current and high cutting speed of 4000 mm/ min. However, the minimum microhardness of the HAZ of 156.7 HV was found in the sample processed at 20 A current and low cutting speed of 500 mm/ min.